Immune Checkpoint Inhibitors for Unresectable Hepatocellular Carcinoma - Mohamed A. Abd El Aziz; Antonio Facciorusso; Tarek Nayfeh; Samer Saadi; Mohamed Elnaggar; Christian Cotsoglou; Rodolfo Sacco (Vaccines, 2020)
Despite the advances in screening protocols and treatment options, hepatocellular carcinoma (HCC) is still considered to be the most lethal malignancy in patients with liver cirrhosis. Moreover, the survival outcomes after failure of first-line therapy for unresectable HCC is still poor with limited therapeutic options. One of these options is immune checkpoint inhibitors. The aim of this study is to comprehensively review the efficacy and safety of immune checkpoint inhibitors for patients with HCC.